A Reference Framework for Utilization of Software Operation Knowledge - van der Schuur, Henk; Jansen, Slinger; Brinkkemper, Sjaak (2010 36th EUROMICRO Conference on Software Engineering and Advanced Applications, 2010)
Knowledge of in-the-field software operation is a broad but ill-defined and fragmentarily supported subject and it is unclear how software vendors can take advantage of such knowledge. This paper introduces and defines software operation knowledge to unify existing definitions, and presents an empirically evaluated framework that is designed to aid product software vendors in gaining insight in the potential role of such knowledge in advancement of their products, practices and processes. The results of extensive case studies performed at three European software vendors show that if used correctly, software operation knowledge enables vendors to increase software quality and improve end-user experience. However, case study results also illustrate that the state of knowledge integration is still pragmatic and immature. Vendors have to adapt their workflows, processes and tools to enable structural software operation knowledge utilization.